À propos de l’offre de traitement en milieu correctionnel : guérir, soigner, aider - Casoni, Dianne (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1996)
This paper adresses the complex unconscious identificatory processes which may silently be active within the clinician when he proposes treatment either to a child or adolescent in an institution or to an adult in a correctionnal setting. Three representations of treatment serve as a backdrop to analyse different identificatory movements on the part of the clinician and how such unconscious motivations may affect his work.